Integrative Design : Essays and Projects on Design Research - Michel, Ralf (Board of International Research in Design, 2019)
Design reflects social developments in those issues which are also embraced by design researchers. A key concept for how designers position themselves in the future, according to the editor's thesis, may well be integrative design. This term denotes design's potential for the integrative development of a society, a potential imperatively linked with economic and political positions. The book Integrative Design collects basic essays on aspects of integrative design, including design after ownership, inclusion, design as an interface with society, the integration of design and technology, and the political agenda of design. The associated website documents current and recently completed research projects that expand on these aspects.